2016
DOI: 10.1002/jps.24674
|View full text |Cite
|
Sign up to set email alerts
|

Utility of PBPK Absorption Modeling to Guide Modified Release Formulation Development of Gaboxadol, a Highly Soluble Compound With Region-Dependent Absorption

Abstract: Given the complexity of controlled release (CR) formulations, selecting the right preclinical tools is important to enable decision making on the in vivo performance of these formulations during development. In recent years, with the advancements of absorption/physiologically based pharmacokinetic (PBPK) modeling, such computational approaches play an increasing role in guiding formulation development. Development of PBPK models for CR formulations requires additional information compared with immediate releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…The model was subsequently used to extrapolate this data to the fed state, where the elimination of a food‐dependent increase in fenofibrate bioavailability utilising the novel formulation was predicted . Kesisoglou et al . have also used the GastroPlus™ minipig model, in conjunction with modelling of dog and human data, in the formulation development of a modified release preparation of gaboxadol.…”
Section: Role Of In Vitro and In Silico Models For Predicting The Suimentioning
confidence: 99%
See 2 more Smart Citations
“…The model was subsequently used to extrapolate this data to the fed state, where the elimination of a food‐dependent increase in fenofibrate bioavailability utilising the novel formulation was predicted . Kesisoglou et al . have also used the GastroPlus™ minipig model, in conjunction with modelling of dog and human data, in the formulation development of a modified release preparation of gaboxadol.…”
Section: Role Of In Vitro and In Silico Models For Predicting The Suimentioning
confidence: 99%
“…The authors successfully incorporated in vitro dissolution data and preclinical pharmacokinetic data within the PBPK models to guide formulation development. Subsequently, it was possible to use the minipig PBPK model to develop an IVIVC to project formulation performance . Using regional permeability data measured in dogs and clinical pharmacokinetics from human studies, the minipig ACAT model was optimised using an immediate release dry filled capsule as a reference.…”
Section: Role Of In Vitro and In Silico Models For Predicting The Suimentioning
confidence: 99%
See 1 more Smart Citation
“…The food-effect study, however, was shown to be challenging. Kesisoglou et al (2016) developed a PBPK model for the dog to describe absorption in the large intestine for a BCS class I drug dosed via ileal and colonic ports to evaluate regiondependent absorption. A minipig absorption PBPK model was also developed by using the default minipig ACAT model in "Gastro-Plus" and assuming regional absorption differences to be the same as in the dog.…”
Section: Pbpk Modelsmentioning
confidence: 99%
“…3. Mechanistic models: In silico models are used to describe the in vivo dissolution or absorption of a drug from a dosage form (13,14). A UIR provides the information upon which subject-specific model physiological and pharmacokinetic attributes (system behavior) are defined.…”
Section: Introductionmentioning
confidence: 99%